2008
DOI: 10.1002/ajmg.a.32324
|View full text |Cite
|
Sign up to set email alerts
|

15q13q14 deletions: Phenotypic characterization and molecular delineation by comparative genomic hybridization

Abstract: We report on a detailed phenotypic characterization of two patients with novel de novo deletions involving 15q13q14, a chromosomal region immediately distal to the Prader-Willi/Angelman syndrome critical interval. Both cases were detected by the clinical array-based comparative genomic hybridization (array-CGH) and were precisely delineated through the high-density Agilent 244 K oligonucleotide array. The comparison of our patients with previously reported deletion cases involving the 15q13q14 region demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…The deletion of MEIS2 has been recently reported in patients with cleft palate and congenital heart defects [3] suggesting its involvement also in the clinical phenotype of our patient. Moreover, Stankunas et al [25] showed that disruptions of MEIS1 , a gene belonging to the same family of MEIS2 and interacting with PBX1-2-3 through the formation of a heteroligomeric complexes, produces heart defects in mice because it controls a subset of target genes that regulate cardiac outflow tract formation.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The deletion of MEIS2 has been recently reported in patients with cleft palate and congenital heart defects [3] suggesting its involvement also in the clinical phenotype of our patient. Moreover, Stankunas et al [25] showed that disruptions of MEIS1 , a gene belonging to the same family of MEIS2 and interacting with PBX1-2-3 through the formation of a heteroligomeric complexes, produces heart defects in mice because it controls a subset of target genes that regulate cardiac outflow tract formation.…”
Section: Discussionsupporting
confidence: 56%
“…We have compared the clinical features of our patient with published reports of patients with larger, cytogenetically visible deletions encompassing chromosome band 15q14, as listed in Table 2[3,26-38]. These comparisons are, however, hampered by additional chromosome aberrations present in about half (7/15) of these patients, and the different deletion sizes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Of interest is the association of 15q14 microdeletion and TOF on prenatal ultrasound in the present case. Congenital heart defects associated with the cases with the 15q14 microdeletion have been well described: Chen et al [14] reported VSD associated with del(15)(q14) (submicroscopic, 5.6 Mb); Crowley et al [15] reported VSD associated with del(15)(q14) (submicroscopic, 123 kb); Johansson et al [17] reported VSD in three of nine cases with del(15)(q14) (submicroscopic, 0.6e4.8 Mb); Brunetti-Pierri et al [13] reported congenital heart defects associated with del(15)(q14) (submicroscopic, 4.2 Mb) and del(15)(q13eq14) (submicroscopic, 8.9 Mb), respectively, in two patients; Erdogan et al [12] reported atrial septal defect (ASD) associated with del(15)(q14) (submicroscopic, 5.3 Mb); Galan et al [8] reported pulmonary valve stenosis associated with del(15)(q12eq14); Tonk et al [9] reported VSD, patent ductus arteriosus (PDA), and ischemic cardiomyopathy associated with del(15)(q12eq14); Autio et al [7] reported ASD associated with del(15)(q13eq15); Herva and Vuorinen [3] reported VSD, hypoplastic pulmonary artery, and atretic tricuspid valve associated with del(15)(q12eq14); Pauli et al [5] reported VSD associated with del(15)(pter-q15) and del(11)(q25-qter); Windpassinger et al [10] reported persistent foramen ovale and PDA associated with del(15)(pter-q14) and del(3)(qter); Duckett and Roberts [4] reported VSD, ASD, PDA, and transposition of great vessels associated with del(15)(pter-q14 or q15) and trisomy 13 (pter-q32 or q33); Schwartz et al [6] reported coarctation of the aorta and PDA associated with del(15)(pter-q14) and del(22)(pterq13.2); and Matsumura et al [11] reported PDA associated with del(15)(pter-q14) and trisomy 22q. Matsson et al [18] analyzed two large Swedish families segregating autosomal dominant secundum ASD5 and identified heterozygosity for a mutation of M123V in the 20 affected individuals.…”
Section: Discussionmentioning
confidence: 95%
“…The clinical features of this patient are summarized in Table 1 and are compared with those of the previously reported patients with 15q14 deletions 4,5,6, 7,8 and MEIS2 mutations. 1,2 As shown, various degrees of developmental delay are commonly observed in the patients with MEIS2 haploinsufficiency.…”
mentioning
confidence: 99%